Therapeutic potential of five frequently prescribed herbs in obesity-associated Hashimoto’s thyroiditis: insights from efferocytosis regulation - Zhou, Jiahao; Gao, Tianshu (Frontiers in Medicine, 2025)
BackgroundPatients with obesity-associated Hashimoto’s thyroiditis (HT) have been prevalent in clinical practice. Obesity is a risk factor for HT as it promotes pro-inflammatory processes and influences the balance of immune cell subsets. Traditional Chinese medicine (TCM) is characterized by its multi-component and multi-target approach and shows potential in treating HT. Specifically, TCM can reduce thyroid antibody levels and alleviate clinical symptoms without impairing thyroid function. Moreover, TCM offers significant benefits in regulating lipid metabolism and decreasing systemic inflammation.MethodsTargets of five high-frequency herbs (Hedysarum multijugum Maxim, Radix Bupleuri, Prunella vulgaris, Fritillaria thunbergii Bulbus, and Angelicae sinensis Radix) were obtained from the TCMSP and Swiss Target Prediction databases. Targets associated with obesity-associated HT were collected from the GeneCards, OMIM, and DisGeNET databases. Subsequently, we employed KEGG signaling pathway enrichment and GO biological process enrichment analyses to investigate the potential mechanisms by which the active ingredients of these herbs treat obesity-associated HT. Then, STRING database networks and Cytoscape software were used to construct the protein-protein interaction network and screen for key targets. Finally, molecular docking was performed to predict the binding interactions between the targets.ResultsEfferocytosis emerged as the key mechanism in the context of five herbs and obesity-associated HT. Quercetin was identified as the primary active ingredient responsible for efferocytosis, and it bound well with efferocytosis-related targets.ConclusionThis study’s key finding is that five high-frequency prescribed herbs may treat obesity-associated HT through efferocytosis. This provides new evidence to support the use of TCM in treating obesity-associated HT.